(untitled) (KULT_online, 2024)
Fiona J. Doloughan interrogates the conflation of fiction and non-fiction by analyzing the literary and philosophical works of four contemporary authors, arguing that memoir and autofiction blur the line between the real and the imagined, resulting in a shift in the current trend of the novel. The study insightfully examines how literature reflects, influences, and interacts with real-life experiences, emotions, and societal issues, and considers how genres are shaped by societal construction of gender roles, expectations, and stereotypes.